الحماية الخاصة للنساء المدنيات في القانون الدولي الإنساني - جبابلة, عمار (University of Eloued جامعة الوادي, 2017)
يمنح القانون الدولي الإنساني للنساء المدنيات حماية مزدوجة، إذ يستفدن من الحماية العامة الممنوحة للأشخاص المدنيين الذين لا يشاركون في الأعمال الحربية، ومن حماية خاصة تهدف إلى توفير حماية إضافية لهن نظرا لاحتياجاتهن الطبية والفسيولوجية المرتبطة غالبا بدورهن في الإنجاب ولاعتبارات الخصوصية . ونظرا لأن الحماية الخاصة أكثر أهمية بالنسبة للنساء المدنيات خصوصا زمن النزاعات المسلحة، سوف نحاول فيما يلي التركيز على دراستها للوقوف على مدى فعاليتها. Abstract International humanitarian law grants women double protection, where they benefit from general protection granted to civilians for people who do not take part in hostilities, and special protection aim to provide additional protection for them because of medical and physiological needs which is often linked to their role of childbearing and privacy considerations. Because of that special protection is more important for women, especially in times of armed conflict, we will address in this study this issue to determine the extent of its effectiveness
Special protection for women in international humanitarian law
مجلة البحوث والدراسات المجلد 14 العدد 01 جامعة الوادي
Keywords: الحماية، النساء، القانون الدولي الإنساني، المدنيين; Protection, women, international humanitarian law, civilians